Assessment of the Magnitude and Extent of Climate Change in Different Regions of Iran - Behzad Rayegani; Susan Barati; Mohammadrezad Farzaneh; Farhad Hosseini Tayefeh; Abed Torabinia (محیط زیست و توسعه فرابخشی)
Introduction: Climate change is recognized as one of the most critical environmental challenges of the 21st century, significantly impacting ecosystems, natural resources, and human livelihoods. The increasing concentration of greenhouse gases, particularly carbon dioxide, has resulted in profound alterations in temperature, precipitation patterns, water availability, and the frequency of extreme weather events. Iran, characterized by its predominantly arid and semi-arid climate, is highly susceptible to these changes. A comprehensive analysis of the intensity and extent of climate change and its effects on natural resources, particularly vegetation, is essential for sustainable resource management. This study aims to assess climate change impacts in Iran from 1958 to 2021 and evaluate its relationship with changes in natural vegetation cover.Materials and Methods: This research was conducted in two main phases. In the first phase, TerraClimate data were used to analyze climatic changes across Iran. Parameters such as minimum and maximum temperatures, cumulative precipitation, runoff, actual evapotranspiration, reference evapotranspiration, climatic water deficit, and the Palmer Drought Severity Index were analyzed annually. Statistically significant trends were identified using correlation and linear regression analyses, and climatic change maps were generated. A comprehensive map depicting the intensity of climate change was developed using the Weighted Linear Combination (WLC) method based on fuzzy logic, focusing on three key parameters: minimum temperature, maximum temperature, and precipitation. In the second phase, changes in natural vegetation cover were analyzed using the NDVI index and MODIS satellite imagery. Natural vegetation areas were identified, and the annual trends in vegetation cover changes were evaluated for statistical significance. The relationship between climatic changes and vegetation degradation was assessed through Pearson correlation analysis, and relevant maps were created.Results: The findings indicated that climate change impacts are evident across Iran but are not uniformly distributed. The northwest, west, the Zagros region, and the northeast experienced the most intense changes. In these areas, annual minimum and maximum temperatures increased by more than 2 to 3°C, while cumulative precipitation decreased by over 100 mm in some regions. Central and eastern Iran faced significant increases in climatic water deficits, leading to substantial vegetation degradation. Northern provinces such as Gilan, Ardabil, and Golestan are severely threatened, with permanent wetlands at significant risk. Vegetation analysis revealed that declining precipitation and rising temperatures, particularly in arid and semi-arid regions, have played a crucial role in vegetation decline, most notably in barren lands and shrublands.Discussion: This study confirms that Iran has faced significant climate change impacts in recent decades, with detrimental effects on its natural resources and ecosystems. Rising temperatures, declining precipitation, and intensifying water deficits pose substantial challenges to resource sustainability. The results underscore the urgency of formulating comprehensive policies and implementing national strategies to mitigate climate change effects, manage water resources, and protect vulnerable ecosystems. Continuous monitoring of climate change and its effects on natural resources is imperative for informed decision-making and effective planning.